2017
DOI: 10.1002/ejic.201700641
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Reactivity of the [W3S4Br3(edpp)3]+ [edpp = (2‐aminoethyl)diphenylphosphine] Cluster Cation towards Bases: The Active Role of the Amino Group

Abstract: Detailed studies through stopped‐flow 31P{1H} NMR spectroscopy and ESI‐MS were performed for the reactions of the [W3S4Br3(edpp)3]+ [edpp = (2‐aminoethyl)diphenylphosphine] cluster with bases such as NaOH and Et3N in acetonitrile. For the reaction with OH– ions, the study allowed the identification of hydroxo species and the development of a procedure for the synthesis of the [W3S4(OH)3(edpp)3]+ cluster in high yields. This involves the substitution of the coordinated bromide ligands by OH– ligands, and the as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…This is not surprising since previous NMR studies on the hydrido [W 3 S 4 H 3 (edpp) 3 ] + (edpp = 2aminoethyl)diphenylphosphine) cluster showed that one of the hydrogen atoms of the NH 2 aminophosphine group is rapidly exchanging with the hydride and as a consequence no hydride signal is seen by 1 H NMR spectroscopy. [36] Unfortunately, all attempts to synthesize and isolate this last postulated species failed.…”
Section: Mechanistic Insightsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is not surprising since previous NMR studies on the hydrido [W 3 S 4 H 3 (edpp) 3 ] + (edpp = 2aminoethyl)diphenylphosphine) cluster showed that one of the hydrogen atoms of the NH 2 aminophosphine group is rapidly exchanging with the hydride and as a consequence no hydride signal is seen by 1 H NMR spectroscopy. [36] Unfortunately, all attempts to synthesize and isolate this last postulated species failed.…”
Section: Mechanistic Insightsmentioning
confidence: 99%
“…Previous spectroscopic studies combined with theoretical calculations on the reactivity of the aminophosphino [W 3 S 4 Br 3 (edpp) 3 ] + cluster towards Et 3 N indicated that the amine acts as a base and abstracts one proton from the NH 2 group of the bidentate ligand while bromine dissociates. [36] Also, Collision Induced Fragmentation (CID) of the [Mo 3 S 4 Cl 3 (edpp) 3 ] + (3 + ) cluster catalyst occurred with HCl release to yield deprotonated [Mo 3 S 4 (edpp-H) 3 ] + species. [29] Based on these antecedents, we tentatively assigned the singlet signal at δ = 65.09 ppm to the [Mo 3 S 4 (ed i p r p-H) 3 ] + (U) unsaturated Mo=NH amido cluster.…”
Section: Mechanistic Insightsmentioning
confidence: 99%